The International Financial Reporting Standards (IFRS) accounting system as applied to forestry - Penttinen, Markku; Rantala, Olli (Finnish Forest Research Institute, 2008)
Forestry has been monitored in agricultural profitability book-keeping as a separate business area since 1912 by the Economic Research of the MTT Agrifood Research Finland. At present, the monitoring is based on the accounting data collected annually from approximately 1050 book-keeping farms. The monitoring is grounded on the profitability book-keeping application, MARTTI, and an Internet based reporting system, EconomyDoctor. Since 1995, the Finnish data for the Farm Accountancy Data Network (FADN) of the member states of the European Union (EU) has also been supplied by MTT Economic Research, which is the authorized Finnish Agency in the FADN network. The book-keeping data collected from farms is used to calculate the closing of accounts, i.e. the profit and loss statement and balance sheet, as well as key economic ratios for each production line. Forestry incomes and expenditures are collected, as well as labour and property data. The key element of developments forest accounting is the availability of the forest inventory contained in the forest management plan (FMP) of a forest holding. Moreover, owners report all updates, such as fellings and silvicultural activities, after the forest inventory. Using the updated forest inventory, the MELA FMP software of the Finnish Forest Research Institute (Metla) provides the values of the growing stock and bare land and returns these to the MARTTI accounting system . These information systems have been integrated via the Internet using the XML protocol and service procedures, firewalls, etc. information and communication technologies (ICT). The established forestry book-keeping procedure provides reliable information for the purpose of financial statements.The financial statements have been drawn up using the International Financial Reporting Standards (IFRS) and especially its International Accounting Standards (IAS) 41 - Agriculture for the growing stock and IAS 16 - Property, Plant and Equipment for the bare land. The key IAS notion of fair value as the evaluation basis can, in the case of forestry be interpreted loosely as net present value (NPV). The fair value of the growing stock fluctuates annually according to the impact of the net increase and fellings. Both physical and price changes affect the net profit according to IAS 41. The key aspect of the development is the evaluation of the IAS fair value of the growing stock, classified as mature and immature biological assets, and their annual changes. The changes due to stumpage price and physical change in the growing stock are also to be disclosed separately. Moreover, the fair value of bare land is also estimated annually for each stand. The purpose of this study is to apply all relevant IAS/IFRS statutes and relevant theoretical contributions to determine whether the international accounting standards (IASs) are applicable in profitability book-keeping for forest holdings in order to support rural entrepreneurship. The structure of the financial statement reports accords to the IAS standards. The applicability of the IAS standards have been tested with the data and technical framework of the profitability book-keeping system of the MTT Economic Research.
Keywords: Ma; laskentatoimi; kirjanpito; kannattavuus; metsätalous; maatilat; accounting; profitability; forestry; farms; IFRS; International Financial Reporting Standards